Using the United States Census Data to Introduce Differential Equations. Issue 7 (9th August 2019) - Linhart, Jean Marie
Abstract: This article describes a method for using the United States Census data to open a differential equations course. The question of finding a model for the United States population data gives students a first experience with creating a model using differential equations, and also understanding derivatives, what they mean, and how to calculate them in the context of real data. This model-building start motivates further exploration in many of the standard differential equations topics: the method of separation of variables, slope fields, autonomous equations, equilibria, and stability.